Uncertain veracity judgments: Does the framing of the question influence deception detection?. (14th April 2023) - Grassi, Massimo; Zloteanu, Mircea
Abstract: In deception research, little consideration is given to how the framing of the question might impact the decision-making process used to reach a veracity judgment. People use terms such as "sure" to describe their uncertainty about an event (i.e., aleatory) and terms such as "chance" to describe their uncertainty about the world (i.e., epistemic). Presently, the effect of such uncertainty framing on veracity judgments was considered. By manipulating the veracity question wording the effect of uncertainty framing on deception detection was measured. The data show no difference in veracity judgments between the two uncertainty framing conditions, suggesting that these may operate on a robust and invariant cognitive process.